PENINGKATAN KESEHATAN MASYARAKAT MELALUI TEKNOLOGI INOVASI PENGGUNAAN TANAMAN OBAT KELUARGA (TOGA) DI KLATEN JAWA TENGAH - Dwi Ratnaningsih; Cici Riansih (Jurnal Pengabdian Masyarakat Permata Indonesia, 2023)
In an effort to improve public health in Karangasem Hamlet, Barukan Village, ManisrenggoDistrict, Klaten Regency, by utilizing traditional plants as natural remedies, the community istaught to plant TOGA in their fields or yards. The purpose of this activity is to increase publicawareness and understanding of the importance of planting TOGA in the land or yard of thehouse. The method of implementing this activity begins with outreach, training andmentoring. The results of this activity increased knowledge and awareness about theimportance of planting TOGA. Suggestions for the people in the Klaten Environment to utilizevacant land as a place to plant TOGA, increase knowledge of the benefits of TOGA as anatural medicine and cultivate it to increase residents' income. In addition, TOGA can also beused as a traditional medicine to improve public health in the Klaten environment, so thatresidents are not dependent on the use of medical drugs.